DEVELOPMENT OF THE INSTITUTIONAL AND LEGAL BASIS OF THE FINANCIAL STABILITY OF THE INSURANCE COMPANY - Abaieva, A.Yu. (The actual problems of regional economy development, 2022)
This article is devoted to the development of institutional and legal basis of the financial stability of domestic insurance companies operating in conditions of increasing risks and threats to the external environment, in particular, the development of recommendations of its improvement is urgent. As a result of a critical analysis of the institutional and legal basis of ensuring financial stability as long-term solvency of resident insurers, in particular with the so-called compliance with Solvency II, it was revealed that institutional and legal basis of financial stability of insurers is now at the stage of improvement, which is an important component of the National program of adaptation of legislation and provides for the unification of legal terminology, amendments and additions to regulatory legal acts, as well as the adoption of new ones. An analysis of the actual situation and prospects for the development of institutional and legal support for the financial stability of insurance companies in Ukraine in connection with the adoption of a new version of the Law of Ukraine "On Insurance". The analysis of the real situation and prospects for the development of institutional and legal support for the financial stability of insurance companies in Ukraine in connection with the adoption of a new version of the law of Ukraine "On insurance" is carried out. It is revealed that the changes relate, in particular, to the introduction of a differentiated approach to the requirements for the solvency of insurers. It is established that the new EU requirements (Solvency II) for solving the problem of strengthening the long-term solvency of insurance companies in order to maximize the protection of property interests of policyholders provide for the establishment of a risk-based system of solvency of the insurer. The main directions of improving institutional and legal basis of managing financial stability as long-term solvency of domestic insurance companies in accordance with European requirements (Solvency II) are identified: changing the approach of the insurance market regulation; changing the requirements to the insurer's capital; improving the assessment of the value of assets and the adequacy of formed reserves; changing the approach to risk management of insurance activities. These changes will contribute to improving the efficiency of state supervision and risk management of insurance activities, in the context of increasing the level of full and timely payment to customers and creditors by insurers, and developing the Ukrainian insurance market as a whole.